Peran TPQ untuk meningkatkan kualitas baca Al-Quran Anak di Masjid Nurul Iman Sukaraja - Maryam; Maya Marisa Oktavia; A'la, Nurul; Harya Anisa; Dinda Erika Tamara; Munisa Anggraini; Ida Sentia Peronisa; Meliyana; Muhammad Zamzami; Depo Setiawan (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This article explores the role of TPQ in enhancing the quality of children's Quranic reading at the Nurul Iman mosque in Sukaraja. The study aims to evaluate how TPQ contributes to improving children's Quranic reading at this mosque. A qualitative research approach is employed in this study, as it enables researchers to gain deeper insights into the meanings and experiences of the participants in the process of learning the Qur'an at TPQ. The study concludes that the TPQ at Nurul Iman mosque in Sukaraja has significantly contributed to enhancing the quality of Quranic reading. This achievement is strongly supported by effective management strategies that organize and guide teaching and learning activities, creating an efficient and conducive learning environment, along with clear institutional goals and objectives aimed at improving Quranic reading skills in early childhood.